2010
DOI: 10.1063/1.3399703
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response of magnetoelectric 1–3-type composites

Abstract: A three-phase magnetoelectric ͑ME͒ composite consisting of Pb͑Zr, Ti͒O 3 rods embedded in a matrix of Terfenol-D/epoxy ͑TDE͒ pseudo 1-3 composites has been fabricated. Besides the large ME effect, its frequency response under a magnetic bias field has been studied. It was found that the resonance shifts to lower frequency with increasing bias field. Due to the magnetomechanical characteristics of the TDE pseudo 1-3 medium, the composite shows a similar trend in ME performance. Magnetic-field dependence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
“…A peak ME response of 6 V/cm¨Oe was obtained between 80 and 110 kHz. Lam et al [20] studied the frequency response of PZT-TDE composite, made using the same dice-and-fill method, under magnetic bias field. It was found that the resonance shifted to a lower frequency with increasing magnetic bias field.…”
Section: Bulk Me Compositesmentioning
confidence: 99%
See 3 more Smart Citations